Prison life of Jefferson Davis : embracing details and incidents in his captivity, particulars concerning his health and habits, together with many conversations on topics of great public interest - Craven, John Joseph, 1822-1893.; Making of America Project; University of Michigan. Digital Library Platform & Services (New York : Carleton, 1866)
This book examines Jefferson Davis's time in prison after the Civil War.
An Introduction by Anecdote -- Fortress Monroe -- Placing Mr. Davis in Irons -- Conversation with Mr. Davis on many Points -- Conversations of some Interest -- Operations on the Southern Coast -- Mr. Davis on the New England Character -- Mr. Davis on Cruelty to Prisoners -- Mr. Davis on Gen. Butler and Dutch Gap -- Diseases of the Eye -- Mr. Lincoln's Assassination -- Mr. Davis seriously Ill -- Southern Migration to Mexico -- Mr. Davis on Negro Character -- Southern Non-Belligerents -- Mr. Davis on Feminism -- Mr. Davis seriously Ill -- Mr. Davis on Sensation News -- Treason -- Visit to Richmond -- Removal to Carroll Hall -- A New Regiment on Guard -- General Summary in Conclusion
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Davis, Jefferson, -- 1808-1889 -- Imprisonment; Davis, Jefferson, -- 1808-1889; Davis, Jefferson, -- 1808-1889; Statesmen -- United States -- Biography; Hommes d'État -- États-Unis -- Biographies; statesmen; HISTORY -- United States -- Civil War Period (1850-1877); Imprisonment; Statesmen; United States; Biography; Biographies; Biographies; Biographies; Biographies